2003
DOI: 10.1002/hlca.200390312
|View full text |Cite
|
Sign up to set email alerts
|

ω‐Fluoro Thiafatty Acids: New Mechanistic Probes of Desaturase‐Mediated Reactions

Abstract: Dedicated to Duilio Arigoni on the occasion of his 75th birthday A series of 18-fluoro thiastearates were prepared and incubated with a yeast D9-desaturating system. The relative efficiency of desaturase-mediated sulfoxidation was monitored via 19 F-NMR analysis of the sulfoxide products, and a strong preference for oxo transfer to the S-atom occupying the 9-position was confirmed. The oxidation profile obtained in this manner matched that of analogous experiments with non-fluorinated substrates. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…[10d] 3b, [7] 3c, [40] 3e, [7] 3f, [7] 3g, [10d] 3h, [12] 3i, [10d] 3j, [10b] , 3k, [10d] 3l, [10d] 3m, [41] 3n, [42] 3o, [43] 3p, [43] 3q, [44] 3r, [45] 3s, [11d] 3v, [28] and 3z [12] are all known, and their structures are consistent with their published physical data.…”
Section: Discussionmentioning
confidence: 99%
“…[10d] 3b, [7] 3c, [40] 3e, [7] 3f, [7] 3g, [10d] 3h, [12] 3i, [10d] 3j, [10b] , 3k, [10d] 3l, [10d] 3m, [41] 3n, [42] 3o, [43] 3p, [43] 3q, [44] 3r, [45] 3s, [11d] 3v, [28] and 3z [12] are all known, and their structures are consistent with their published physical data.…”
Section: Discussionmentioning
confidence: 99%
“…[43] Conclusion A large number of fluorinated analogues of unsaturated fatty acids and corresponding metabolites have been prepared to date. Versatile strategies have been developed in order to introduce selectively a single fluorine atom, as well as CF 2 or CF 3 groups, in the desired positions of these highly sensitive compounds.…”
Section: Natural Fluorinated Fatty Acids and Biosynthetic Studiesmentioning
confidence: 99%
“…3 Previous experiments have shown that this whole cell system efficiently incorporates fatty acyl substrates from the medium into the intracellular CoA thioester substrate pool 12 where they are processed by the endogenous D 9 desaturase. Polar sulfoxy products produced in this manner are then hydrolyzed and excreted into the medium as the free acid.…”
mentioning
confidence: 99%
“…7 Compound 1 was synthesized by S-alkylation of 10-mercaptodecanoic acid 8 with 1-bromo-4-fluorobutane followed by methylation (BF 3 / MeOH) using previously published procedures. 3 The crude product was purified by flash chromatography (SiO 2 , 5% EtOAC/hexane) to give 1 in an overall yield of 8% based on 10-bromodecanoic acid. The corresponding racemic sulfoxide 2 and sulfone 3 were prepared by oxidation of 1 with one and two equivalents of meta-chloroperbenzoic acid (MCPBA), respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation